2020
DOI: 10.1101/2020.09.29.20203786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of maternal pre-/early-pregnancy BMI and pregnancy smoking and alcohol on congenital heart diseases: a parental negative control study

Abstract: Background: Congenital heart diseases (CHDs) are the most common congenital anomaly. The causes of CHDs are largely unknown, but intrauterine mechanisms appear to be important. Higher prenatal body mass index (BMI), smoking and alcohol consumption are associated with increased risk of CHDs. Whether these are causal is unclear. Methods: Seven European birth cohorts including 232,390 offspring were included. We applied negative exposure paternal control analyses to explore the intrauterine effects of maternal B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…An analysis plan was written and published in October 2019, with any subsequent changes and their rationale documented in the publication. 35 All associations between exposures and CHDs were performed within participating studies using logistic regression (binary for main analyses and multinomial for CHD severity analyses). In the 2 largest cohorts (DNBC study and MoBa), we assessed deviation from linearity in our models in the BMI analyses by running our main confounder‐adjusted model with BMI split into fifths.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis plan was written and published in October 2019, with any subsequent changes and their rationale documented in the publication. 35 All associations between exposures and CHDs were performed within participating studies using logistic regression (binary for main analyses and multinomial for CHD severity analyses). In the 2 largest cohorts (DNBC study and MoBa), we assessed deviation from linearity in our models in the BMI analyses by running our main confounder‐adjusted model with BMI split into fifths.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of CHDs in ALSPAC is similar to other European birth cohorts. In recent work involving 7 European birth cohorts, we have shown that the prevalence of CHD was close to 1% in most cohorts, with the lowest with 0.4% and the highest with 1.4% 26 . Differences in case ascertainment could be one of a number of possible explanations for the slight differences in prevalence estimates.…”
Section: Description Of Populationmentioning
confidence: 78%
“…Even with adjustment, residual confounding (from using poorly measured confounders or not adjusting for important confounders) can bias results. Useful strategies for checking if residual confounding influences results include negative control variables and comparing cohorts with different confounding structures [38,[67][68][69].…”
Section: Identifying Determinants and Outcomes Of Trajectoriesmentioning
confidence: 99%